Aplicação de manutenção preventiva em puncionadeira - Romão, Gabriel Yuji Okuyama (2013)
This Degree Completion Work aimed to apply modern maintenance techniques in the most critical equipment in MQA-PAR Metallurgical Industry, in order to reduce unexpected machinery interruptions and, consequently, decrease costs and improve its productivity indicators. The proposed methodology was to conduct studies defining the equipment criticality in the company and define the proper maintenance technique in the presented scenario. Maintenance technique chosen was developed based on the eight pillars of the Total Productive Maintenance and applied in the most critical machine of MQA-PAR. Indicators extracted from the new maintenance method implementation were positive as well its production effects.